Physical education specialist`s emotional burnout test and prevention provisions - Selivanova, E. A.; Ilyasov, D. F.; Cherepov, E. A.; Smirnova, L. V. (Theory and Practice of Physical Culture, 2019)
The study was run in the period of 2011-2017 to accumulate the 2011/ 2014/ 2017 test data arrays for comparative analyses based on the Physical Education specialist job-specific emotional state profiling test data. It was found that the proportion of the emotional-burnout-symptoms-free Physical Education specialists have dropped for the 7 years from 28% to 18%, with most of the sample (55%) diagnosed with some emotional burnout symptoms including tension, resistance and exhaustion. The high-emotional-burnout share of the sample amounted to 9%, 11% and 13% in 2011, 2014 and 2017, respectively, with the growth explainable by a variety of stressors including the never-ending reforms in the national education system with their human resource related innovations including the new professional competence test standards, inclusive education standards, FSES, national teacher advancement and promotion system etc. The teaching service conditions are increasingly challenging for many due to the regress in the students` health situation, with many students being increasingly aggressive - often due to the physical/ mental deviations. The educational system is obviously in need of the emotional burnout prevention service to protect health of the teachers on the whole and the Physical Education specialists in particular. Based on the study findings, we offer a set of the emotional burnout prevention recommendations that require the modern school resource making a special emphasis on the teacher`s self-learning agenda and motivations. The teachers` unpreparedness for reforms shall be addressed by the focused efforts to improve their legal, psychological, educational and practical competences and versatility in the modern education environments, methods and tools.